“Sleepless nights are a daily reality for us” how women experiencing homelessness in Addis Ababa, Ethiopia describe street life: a photovoice study - Yohannes, Kalkidan; Målqvist, Mats; Bradby, Hannah; Berhane, Yemane; Tewahido, Dagmawit; Herzig van Wees, Sibylle (Frontiers in Public Health, 2025)
IntroductionHomelessness among women of reproductive age is a global problem. Several unique gender-based issues affect homeless women’s well-being, including reproductive health issues, their homelessness experiences, and a high rate of sexual violence. In this study, we aimed to describe women’s experiences of street homelessness in their own terms and their suggestions to address their unmet needs.MethodsThis photovoice study draws on photos, focus group discussions, and semi-structured interviews. We conducted the study in collaboration with women in their reproductive years experiencing homelessness (n = 9). A total of 80 photos were taken, and 40 were chosen to be discussed in interviews and further focus group discussions. The participating women selected photographs, explained their significance, and codified them based on how they related to their lives. Data from these discussions were then analysed using a reflexive thematic approach.ResultsFour themes were developed from the data: (a) deprivation of basic needs; (b) experiencing dependency, shame, and seclusion while dealing with the burden of street life; (c) the vulnerability and neglect of children; and (d) being resilient to harsh conditions. In this study, women’s street life was characterised by numerous unfavourable aspects, including unmet needs, human rights violations, social exclusions, substance use, and child protection issues. Participants provided suggestions for change and confirmed their belief that adequate housing represents one of the most urgent unmet basic needs of people experiencing homelessness. They also emphasised the critical need for employment opportunities, non-discriminatory provision of social support, treatment programs for substance misuse, and legal and social protection.ConclusionThis study contributes to understanding how women experiencing homelessness describe and articulate their living circumstances and what they perceive needs to be addressed. Based on participants’ proposal for change, comprehensive services are needed to address women’s multifaceted issues. However, the mitigation strategies and long-term effects of women’s homelessness require further research.